Type 2 Diabetes Mellitus in Mexico, Elements to Consider to Strengthen the Health Promotion Component in the National Strategy for Prevention and Control (Global Journal of Medical Research, 1970)
Type 2 diabetes mellitus DM2 is a disease of primary importance for public health not only in Mexico but throughout the world because it is the most common non-communicable disease caused by a combination of genetic environmental and behavioral factors which is why it is necessary to identify patients at high risk of DM2 le disease However is important to bear in mind that intervention by the health system through the Specific Action Program for the Prevention and Control of Diabetes Mellitus 2013-2018 could benefit the population at risk and impact the quality of life of sick patients through health promotion Finally proposals were included to strengthen the National Strategy with emphasis on health promotion
Keywords: diabetes mellitus tipo 2; factores de riesgo; sistema de salud; educación para la salud; promoción de la salud